Registos de passagens : as escritas no porto da Horta - Bouillet, Anna, 1992- (2018)
Marina of Horta, main city of Faial Island, Azores, presents a surprisingly typographical view, due to its diversity and its geographical position, isolated in the midst of the North Atlantic Ocean. Due to a tradition of unknown origin, each sailor docking at the harbour paints their name and date of passage. Exposed to open air, the markings disappear under the action of natural elements and time. Nevertheless, the harbour area remains colourful; like the image of a ‘palimpsest’, the paintings are renewed with the constant flux of sailors docking at Horta. Although attributed to a superstition (“those who don’t paint will have bad luck on their trip”), the reason for this graphic phenomenon is related to leaving behind a mark of your own in a place lived through the experience of travel. As fascinating as they are, the paintings were never investigated from a graphic perspective. Therefore, this essay aims to study in which way the sailors write their passage through the harbour of Horta. It pretends to be fulfilled through a revision of literature that shows the connection between passage and writing, as well as contextualization and an analysis of the Marina’s lettering. A field trip was appointed to develop this last issue, namely by interviewing locals and sailors, research of local bibliography, and by creating a registry of one thousand photographs of the paintings based on an exploratory methodology. The practical part of this Master’s Final Essay, consists of creating a book that presents the photographic material collected throughout the research. Therefore, this editorial project aspires to prolong the passage movement mentioned since the beginning of this investigation, by means of a printed object that will circulate the variety of letters painted on the concrete of Horta’s Marina to other horizons